Grammaticalized verbs in Lolo-Burmese - Smeall, Christopher (2024)
Below I will present an analysis of a set of verbs in urmese which concatenate with each other and with full verbs to form complex predicates which themselves function as unitary predicates in simple sentences. These complex predicates I will call V*'s and the process which forms them 'verb incorporation.' Okell has called these verbs auxiliary verbs and has characterized them as those elements which "precede clause-markers in verb clauses" and "occur in compounds following a wide variety of other verbs." I will attempt to demonstrate that this set of over fifty verbs can be further subcategorized into five groups, which form a sloppy hierarchy of increasing grammaticalization, a trait whose definition will take into account boundness, the presence or absence of complements and complementizers in underlying structure, the possibility of direct negation, flexibility of scope, and surface ordering. I will show that there is a degree of semantic coherence to these predicates and their subcategorizations, and suggest several ways in which their semantic properties might be linked to their grammaticalized syntactic behavior. I will also claim that there is a degree of arbitrariness in the subcategorizations--that the behav¬ior of the system cannot be predicted from semantic facts alone. Where appropriate, I will compare analogous verbs and processes in Lahu and Lisu.